The role of the assistant practitioner in the clinical setting: a focus group study. Part 1. Issue 2 (2nd February 2019) - Henshall, Catherine; Doherty, Andrea; Green, Helen; Westcott, Liz; Aveyard, Helen
Abstract : Background: Assistant practitioners have knowledge and skills beyond the level of traditional support staff, and work in many clinical settings. However, some assistant practitioners lack a clearly defined role and may be under-used due to issues around accountability and uncertainty about their purpose. This paper explores the assistant practitioner role from the perspectives of assistant practitioners and registered nurses. Methods: This study aimed to explore the role of the assistant practitioner from the perspectives of assistant practitioners and registered nurses in two NHS hospital trusts in Oxfordshire, UK. Six qualitative focus groups were undertaken between February–March 2017. Ethical approval was obtained (FREC 2016/05) and written consent was provided by participants. Data was analysed thematically analysed using the Framework method. Results: Some 19 participants (assistant practitioners, n = 12; registered nurses, n = 7) were recruited using convenience sampling. Emerging themes related to 'fluctuating roles and responsibilities of assistant practitioners', 'role differences between registered nurses and assistant practitioners', 'working relationships', 'supervision' and 'redefining nursing pathways'. The Results and Discussion sections highlight a lack of role clarity and blurring of boundaries between the roles of assistant practitioners and registered nurses, with many tasks undertaken by both. This lack of ownership of 'nurse-specific' roles by registered nurses was evident and clear differences were only encountered with regard to accountability. The development of the nursing associate role provides managers with the opportunity to redefine staff banding hierarchies to ensure that clinical staff are aware of their role capabilities and limitations and are practising safely, while promoting career development and progression pathways. Conclusion: Addressing issues around role clarity can benefit professional development, satisfaction, role identity and ownership for registered nurses and assistant practitioners, by recognising the individual and collective value they bring to the clinical team. The findings can help inform the development of the nursing associate role.